The Factors that are Related to Self-Care Agency in Patients with Hypertension - Dendy Kharisna; Helwiyah Ropi; Urip Rahayu (Faculty of Nursing Universitas Padjadjaran, 2018)
Uncontrolled hypertension leads to complex problems experienced by patient as the complication of the hypertension. The patient’s ability to do self-care (self-care agency) is essential and recommended to control hypertension. Age, sex, education, occupation, marital status, decision making, duration of hypertension, lifestyle, and insurance availability are contributed to the self-care agency. Nurses and patients should be able to know and understand these self-care agency related factors. The aim of this study was to identify self-care agency relating factors of hypertension patients in Pekanbaru. This study conducted using a quantitative approach with cross sectional design and involving 100 hypertension patients who recruited using purposive sampling techniques. Self-care agency was measure using exercise of self-care agency (ESCA) questionnare. Data were analyzed using Spearman test and Chi Square test to determine the relation of each factors on self-care agency and multivariate logistic regression test to determine the most related factors on self-care agency. The result showed that there were a significant different of age (p=0.048), education (p=0.002), gender (p= 0.025), health insurance (p=0.027), and life style (p=0.003) with self-care agency. Meanwhile, there were no signifcant different of occupation (p=1.000), decision making (p=0.800), marital status (p=1.000), and duration of hypertension (p=0.567) with self-care agency. Multivariate analysis revealed that the most influence factor for self-care agency is life style. This study suggest the nurses in improving self-care agency of hypertension patients must concern about patient lifestyle and help patient to modify their lifestyle.